Product and trial design considerations on the path towards a vaccine to combat opioid overdose - Asimenia Angelidou; Jacob A. Koster; Amy C. Sherman; Caitlyn McLoughlin; Pooja Lalwani; Aisling Kelly; Ahsan Saeed; Kerry McEnaney; Lindsey R. Baden; Melissa Brogna; Elissa R. Weitzman; Sharon Levy; et al. (npj Vaccines)
Abstract Opioid overdose deaths are an evolving public health emergency in the United States. Recent advancements in drug conjugate vaccine design and adjuvantation technologies have re-ignited interest in the potential clinical utility of opioid vaccination. Here we present the concept of fentanyl vaccination as a complementary strategy for opioid overdose prevention with a focus on vaccine safety, efficacy, and considerations for vaccine development and testing in early phase human clinical trials.